Hybrid Active–Passive Prosthetic Knee: A Gait Kinematics and Muscle Activity Comparison with Mechanical and Microprocessor-Controlled Passive Prostheses - Wang, Xiaoming; Meng, Qiaoling; Bai, Shaoping; Meng, Qingyun; Yu, Hongliu (Journal of bionics engineering, 2023)
Existing microprocessor-controlled passive prosthetic knees (PaPKs) and active prosthetic knees (AcPKs) cannot truly simulate the muscle activity characteristics of the active–passive hybrid action of the knee during the normal gait. Differences in EMG between normal and different prosthetic gait for different phases were never separately analyzed. In this study, a novel hybrid active–passive prosthetic knee (HAPK) is proposed and if and how muscle activity and kinematics changes in different prosthetic gait are analyzed. The hybrid hydraulic-motor actuator is adopted to fully integrate the advantages of hydraulic compliance damping and motor efficiency, and the hierarchical control strategy is adopted to realize the adaptive predictive control of the HAPK. The kinematic data and EMG data of normal gait and different prosthetic gait were compared by experiments, so as to analyze the changes in the muscle activity and spatio-temporal data per phase compared to normal walking and the adaptations of amputees when walking with a different kind of prosthesis (the mechanical prosthesis (MePK), the PaPK and the HAPK). The results show that changes in prosthetic gait mainly consisted of decreased self-selected walking speed, gait symmetry and maximum knee flexion, increased first double support phase duration, muscle activation in both opposed and prosthetic limb and inter-subject variability. The differences between controls and MePK, PaPK and HAPK decreases sequentially. These results indicate that the hybrid active–passive actuating mode can have positive effects on improving the approximation of healthy gait characteristics.